PENGARUH KOMUNIKASI INFORMASI EDUKASI INSTAGRAM TERHADAP SIKAP REMAJA TERKAIT P4GN DI SMAN 4 PADANG - Efri Nurdin; Ernita Arif; Aidinil Zetra (Jurnal Bilqolam Pendidikan Islam, 2024)
This qualitative study investigates the influence of Instagram as an educational information communication platform on adolescents’ attitudes towards the Drug Abuse and Illicit Trafficking Prevention and Eradication Program (P4GN) at SMAN 4 Padang. Through in-depth interviews and thematic analysis, this study aims to explore the different ways in which adolescents interact with P4GN-related content on Instagram, interpret its messages, and see its impact on their attitudes towards drug abuse prevention. By focusing on qualitative research, this study seeks to capture the different ways in which adolescents interact with educational content on Instagram and how these interactions shape their attitudes towards P4GN. Initial findings indicate that adolescents perceive Instagram as a significant source of information about drug abuse prevention, which influences their attitudes and behaviors towards P4GN. The visual nature and peer-driven interactions play a significant role in shaping adolescents’ perceptions and attitudes towards drug abuse prevention efforts. This study provides valuable insights into understanding the effectiveness of Instagram as a tool to promote positive attitudes towards P4GN among adolescents. These findings will inform future educational strategies and interventions in drug abuse prevention, emphasizing the importance of leveraging social media platforms such as Instagram to engage and empower adolescents in promoting a drug-free society.